Formulation and Evaluation of Polymer‐Based Nanoparticles for Intravitreal Gene‐Delivery Applications. Issue 12 (5th December 2022) - Lee, Daiheon; Kwak, Gijung; Johnson, Thomas V.; Suk, Jung Soo
Abstract: The advent of the first‐ever retinal gene therapy product, involving subretinal administration of a virus‐based gene delivery platform, has garnered hope that this state‐of‐the‐art therapeutic modality may benefit a broad spectrum of patients with diverse retinal disorders. On the other hand, clinical studies have revealed limitations of the applied delivery strategy that may restrict its universal use. To this end, intravitreal administration of synthetic gene‐delivery platforms, such as polymer‐based nanoparticles (PNPs), has emerged as an attractive alternative to the current mainstay. To achieve success, however, it is imperative that synthetic platforms overcome key biological barriers in human eyes encountered following intravitreal administration, including the vitreous gel and inner limiting membrane (ILM). Here, we introduce a series of experiments, from the fabrication of PNPs to a comprehensive evaluation in relevant experimental models, to determine whether PNPs overcome these barriers and efficiently deliver therapeutic gene payloads to retinal cells. We conclude the article by discussing a few important considerations for successful implementation of the strategy. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Preparation and characterization of PNPs Basic Protocol 2 : Evaluation of in vitro transfection efficacy Basic Protocol 3 : Evaluation of PNP diffusion in vitreous gel Basic Protocol 4 : Ex vivo assessment of PNP penetration within vitreoretinal explant culture Basic Protocol 5 : Assessment of in vivo transgene expression mediated by intravitreally administered PNPs